2013
DOI: 10.1038/srep01865
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylated derivatives of dimethoxy-1,4-benzoquinone as redox switchable earth-alkaline metal ligands and radical scavengers

Abstract: Benzoquinones (BQ) have important functions in many biological processes. In alkaline environments, BQs can be hydroxylated at quinoid ring proton positions. Very little is known about the chemical reaction leading to these structural transformations as well as about the properties of the obtained hydroxyl benzoquinones. We analyzed the behavior of the naturally occurring 2,6-dimethoxy-1,4-benzoquinone under alkaline conditions and show that upon substitution of methoxy-groups, poly-hydroxyl-derivatives (OHBQ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 29 publications
(37 reference statements)
1
53
0
Order By: Relevance
“…Although the number of studies related to the chemical and redox features of CoQ family members has increased tremendously in the last three decades [8][9][10][11][12][13][14][15][16][17][18], many key features are still not well understood. In our last two publications we have shown that Coenzyme Q-1 (CoQ-1) and CoQ-10 undergo structural changes in strong alkaline environment or in the presence of Cytochrome P450 enzymes [19,20]. As main reaction products we identified several hydroxy derivatives of CoQ-1 and CoQ-10 [19,20].…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Although the number of studies related to the chemical and redox features of CoQ family members has increased tremendously in the last three decades [8][9][10][11][12][13][14][15][16][17][18], many key features are still not well understood. In our last two publications we have shown that Coenzyme Q-1 (CoQ-1) and CoQ-10 undergo structural changes in strong alkaline environment or in the presence of Cytochrome P450 enzymes [19,20]. As main reaction products we identified several hydroxy derivatives of CoQ-1 and CoQ-10 [19,20].…”
Section: Introductionmentioning
confidence: 84%
“…The redox features of many hydrophilic and lipophilic Q and HQ have been intensively studied by various electrochemical methods [4,19,20,[24][25][26][27][28][29], but surprisingly, there are only few reports related to the electrochemical features of the simplest CoQ member, i.e. CoQ-0 [21][22][23].…”
Section: Voltammetry Of Coenzyme Q-0 In Buffered Water Solutionmentioning
confidence: 99%
See 3 more Smart Citations